Thesaurus musicarum latinarum: Canon of Data Files - Mathiesen, Thomas J. (Bloomington, IN Thesaurus musicarum latinarum, 1995)
The "Thesaurus Musicarum Latinarum" is a full-text database of music theory written in Latin, extending from Augustine's De musica through treatises of the sixteenth century. This new edition of the "Thesaurus Musicarum Latinarum: Canon of Data Files" includes full instructions on the various ways in which users can access the database, as well as the "Principles of Orthography" and "Table of Codes for Noteshapes, Rests, Ligatures, Mensuration Signs, Clefs, and Miscellaneous Figures", both of which provide essential explanations of the special ways in which the texts have been encoded to facilitate searching and maximize use within various computer environments. Also included is a table of contents for the major series of texts found in the tml. The "Canon" provides for each separate edition a bibliographic record of the name of the author; title of the treatise; incipit; source of the text; the names of the individuals responsible for entering, checking, and approving the data; the name and location of the data file as it appears within the tml; the size of the file; and annotations identifying accompanying graphics and various other types of pertinent data. The "Canon" is followed by a full alphabetical index of incipits, keyed to both the "Canon" itself through author and title and to the database through the name of the data file as it appears within the tml. Thomas J. Mathiesen is David H. Jacobs Distinguished Professor of Music at Indiana University and the director of the Center for the History of Music Theory and Literature. He is the author of "Ancient and Greek Music Theory: A Catalog Raisonne of Manuscripts" and the general editor of the "Greek and Latin Music Theory"
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); Music theory; Catalog; Latin